Acceptability and feasibility of delegating HIV counseling and testing for TB patients to community health workers in the Philippines: a mixed methods study - Tyrone Reden L. Sy; Retna Siwi Padmawati; Emmanuel S. Baja; Riris Andono Ahmad (BMC, 2019)
Abstract Background The Philippines has a high burden of TB and HIV, yet the WHO estimates that only 13% of Filipino TB patients know their HIV status. This is partly attributable to the lack of trained HIV counselors and medical technologists (or laboratory technicians) at the primary healthcare level. In Africa where resources and manpower are also scarce, TB/HIV care is already delegated to community health workers. Evidence is scant however about the acceptability and feasibility of engaging community health workers to provide HIV counseling and testing (HCT) among TB patients in the Philippines. The objective of this paper is to describe and assess the acceptability and feasibility of delegating HCT among TB patients to barangay (community) health workers (BHWs) in the Philippines. Methods Mixed methods study that utilized surveys with patients (n = 89), BHWs (n = 81), and ten focus group discussions with key stakeholders (n = 49) in San Jose del Monte, a city with high HIV prevalence. A facility assessment (n = 17) was done using a modified version of WHO-Service Availability and Readiness Assessment questionnaire to assess feasibility (scale of 1 to 4) while acceptability from the perspective of patients and BHWs was determined using surveys. Results Only 47% of TB patients agreed to receive HIV counseling from BHWs, while 30% agreed to receive HIV testing. Doctors were preferred by patients as HIV counselors, while medical technologists were preferred as HIV test providers. Two out of three BHWs also disagreed to provide HCT but the same number felt that they could provide HCT if additional trainings were given to them. In the group discussions, BHWs preferred to only provide HIV counseling. Stakeholders said that only select BHWs who meet certain criteria should provide HIV counseling. Program managers and stakeholders rated delegation of HCT to BHWs as moderately feasible. Conclusions Delegation of both HIV counseling and testing among TB patients to BHWs is feasible, but only delegation of HIV counseling is acceptable. Further studies are needed to guide revision of Philippine HCT policies to accommodate lay HIV counselors, and strengthen the mechanisms for delivering integrated TB and HIV services especially at the primary healthcare level.